POLITICAL SPEECHES IN TRANSLATION: AN OUTSTANDING CHURCHILL - Михайленко, О. (Київський національний університет імені Тараса Шевченка, Навчально-науковий інститут філології, 2021)
This paper deals with the problems related to the translation of a political speech as a genre of political discourse, with the aim to investigate the translation solutions used to achieve the pragmatic equivalence of the original and translation texts. The theoretical framework of the article has been equivalence-based translation studies by the prominent scholars in the field. The paper starts by outlining the oratory style features that should be a guide for the translator of political texts. Special research attention is paid to W. Churchill's oratory style, with the focus on the linguo-argumentative strategies that he used to persuade the audience. Consideration of the theoretical framework is followed by the contrastive analysis of the Ukrainian- and Russian-language translations of one of W. Churchill S most influential speeches - “Their Finest Hour”. The paper highlights the translation solutions used by the Ukrainian and Russian translators in rendering W. Churchill's unique expressive style. The translation techniques in Ukrainian and Russian versions of the speech have been compared, with the view to trace the cross-linguistic variations in translation techniques and to determine whether the Ukrainian and Russian translators succeeded in conveying the strong emotional impact that W. Churchill's speech had on the audience. The paper concludes with summarising the appropriateness of the translation techniques in achieving the pragmatic equivalence of the original and translation texts. The research results prove that rendering political speeches is not just a matter of their faithful translation. It is a matter of understanding background cultural, historical and political situations, what influences the choice of translation solutions.

Статтю присвячено порівняльному аналізу політичної промови В. Черчилля “Their Finest Hour” в українському та російському перекладах, із метою дослідження перекладацьких рішень для досягнення прагматичної еквівалентності текстів оригіналу та перекладів. Особливу увагу приділено відтворенню в перекладах мовних засобів експресії як частини лінгвоаргументативних стратегій В. Черчилля. _____________ СПИСОК ВИКОРИСТАНИХ ДЖЕРЕЛ Брандес, М. П., Провоторов В. И. Предпереводческий анализ текста. Москва: НВИ-ТЕЗАУРУС, 224 с. Некряч, Т., Довганчина, Р. Навчаймося виступати публічно = Make your way to public speaking: навч. посібник. Вінниця: Нова Книга, 280 с. Мовні і концептуальні картини світу. Випуск 68 (1) • 2021 93   Baker, M. In Other Words: A Coursebook on Translation. London: Routledge, 2011. 332 p. Bassnett, S. Translation Studies. London: Routledge, 2002. 176 p. Bayar, M. To Mean or Not to Mean. Damascus: Khatawat for Publishing and Distribution, 2007. 223 p. Bell, R. Translation and Translating: Theory and Practice. London, New York: Longman, 1993. 298 p. Catford, J. A Linguistic Theory of Translation. Oxford: Oxford University Press, 1978. 103 p. Chilton, P, Schaffner, C. Politics as Text and Talk: Analytic Approaches to Political Discourse. Amsterdam: John Benjamins, 2002. 246 p. Hatim, B., Munday, J. Translation: An Advanced Resource Book. London: Routledge, 2005. 400 p. His Speeches: How Churchill Did It? URL: https://winstonchurchill. org/publications/finest-hour/finest-hour-112/how-churchill-did-it. House, J. Translation Quality Assessment: A Model Revisited. Tubingen: Narr, 1997. 160 p. Kampf, Z. Political Discourse Analysis. The International Encyclopedia of Language and Social Interaction / K. Tracy, T. Sandel, C. Ilie (Eds.) URL: https://www.academia.edu/5074479/Political_Discourse_Analysis. Kenny, D. Routledge Encyclopedia of Translation Studies / M. Baker (Ed.). London: Routledge, 2001. P 77-80. Koller, W. Equivalence in Translation Theory. Readings in Translation Theory / Chesterman (Ed.). Helsinki: Oy Finn Lectura Ab, 1989. P. 99-104. Mykhailenko, O. Modern Popular Science Translations: The New Digital Age. Lingua Montenegrina. XI/2, br. 22, 2018. P. 39-57. Newmark, P. Approaches to Translation. Oxford: Pergamon Press, 1981. 200 p. Nida, E., Taber, Ch. The Theory and Practice of Translation. Leiden: Brill, 1982. 218 p. Pym, A. Exploring Translation Theories. New-York: Routledge, 2014. 255 p. Pym, A. A Typology of Translation Solutions. The Journal of Specialised Translation. Issue 30, 2018. URL: https://www.jostrans.org/issue30/pdf. Rhetorical Analysis of Winston Churchill's “Their Finest Hour”. URL: https://alexandernealblog.wordpress.com/rhetorical-analysis-of-win- tons-churchills-their-finest-hour. Schaffner, C. Political discourse analysis from the point of view of translation studies. Journal of Language and Politics. 3(1), 2004. P.117-150. Their Finest Hour: The Techniques That Churchill Used to Boost a Nation's Morale. URL: https://medium.com/@speakersinstitutesm/their- finest-hour-the-techniques-that-churchill-used-to-boost-a-nations-morale- a8954f7154f0. Vinay, J-P., Darbelent, J. A Methodology for Translation / Trans. by Juan C. Sager, M. J. Hamel. The Translation Studies Reader / L. Venuti (Ed.). London, New York: Routledge, 1958/1995. P. 84-93. Vitale, T. Winston Churchill's Way with Words. URL: https://www. npr.org/2012/07/14/156720829/winston-churchills-way-with-words. ДЖЕРЕЛА ІЛЮСТРАТИВНОГО МАТЕРІАЛУ Промови, що змінили світ / пер. з англ. В. Горбатько. Київ: КМ- БУКС, 328 с. Речи, которьіе изменили мир / пер. с англ. И. Матвеевой. Москва: Манн, Иванов и Фербер, 2014. 256 с. Churchill, W. Their Finest Hour. URL: https://winstonchurchill.org/ resources/speeches/1940-the-finest-hour/their-finest-hour.
ПОЛІТИЧНІ ПРОМОВИ У ПЕРЕКЛАДІ: ВИДАТНИЙ ЧЕРЧИЛЛЬ
Keywords: political speech; political discourse; linguo-argumentative strategies; expressive means; stylistic devices; translation solutions; translation techniques; політична промова; політичний дискурс; лінгвоар- гументативні стратегії; стилістичні засоби; прагматична еквівалент¬ність; перекладацьке рішення